The adaptation of the Millon Index of Personality Styles to a Peruvian population of university students - Sánchez López, María del Pilar (2002)
The purpose of the study was the adaptation of the MIPS (1994) toa population of 390 university students of Lima ( 188 men and 202 women). The inventory was adapted to the Spanishs poken in Peru. The psychometrical analysis revealed a reliability index of .70 as well as astructural internal validity. Most of the scales presented acceptable levels of internal consistency.The comparison with the studies carried out in Spain and USA showed that the levels of internal-consistency were similar to those found in the Spanish population and slightly below tothose found in the North American population. The analysis of the differences between the averages in each one of the se al es indicated greater discrepancies between the Peruvian populationand the Spanish, than between the Peruvian popular ion and the Nonh American.